Determining the Impact of Adaptive Games on the Individuals’ Psycho-Emotional State among Different Age Groups in Poland and Ukraine - Skaliy, Aleksander; Mulyk, Viacheslav; Skaliy, Tetiana; Maksymova, Kateryna; Mulyk, Kateryna (Physical Education Theory and Methodology, 2024)
Objectives. The study aimed to determine the effectiveness of implementating projects for the introduction of adaptive sports games on the psycho-emotional state of different population groups in Poland and Ukraine. Materials and methods. A total of 341 individuals were involved in the study: 117 children (8-12 years old), 118 middle-aged people (35-60 years old), and 116 elderly people (60 years and older). The participants of the study were divided into two groups: those who took part in the Polish project “Academic Center of Sports and Health Games for Activation of People with Special Needs” (56 children, 65 adults, 73 elderly people), and those who took part in the Polish-Ukrainian project, which was conducted directly in Ukraine, “Ukrainian Center of Occupational Therapy through Adaptive Games” (61 children, 53 adults, 44 elderly people). All study participants were engaged in adaptive games (Cornhole, Jacollo, Elastik, Kulbutto, Boccia, Paka laka) for the first time. At the beginning and end of the event on adaptive games, a survey of participants was conducted. To determine the psycho-emotional state of children, the WAM method (well-being, activity, mood) was used, and the features of adults’ psychological state were assessed using the standard test AWAMW (anxiety, working capacity, activity, mood, well-being). Results. The analysis of the obtained study results revealed positive changes in the psycho-emotional state of different population groups in Poland and Ukraine under the influence of adaptive sports games. Furthermore, the adult population, including the elderly of Poland and Ukraine, demonstrated decreased anxiety levels and a significant enhancement in activity, mood and well-being due to engaging in adaptive sports games. Conclusions. This study emphasizes the potential of adaptive sports games to improve the mental health of different population groups. The findings also indicate the effectiveness of implementating projects for the introduction of adaptive games on the psycho-emotional state of different population groups both in Poland and Ukraine.